Efektivitas Akun Instagram @Unibinfo Sebagai Media Literasi Dalam Pencarian Informasi Mahasiswa Universitas Bengkulu - Santika, Tri (UPT Perpustakaan Universitas Bengkulu, 2023)
This research tries to analyze the effectiveness of the @Unibinfo Instagram account in seeking information literacy for Bengkulu University students. Based on this research, the method used is a quantitative method. The data collection technique used by researchers is a questionnaire. Data analysis in this research includes data reduction, data presentation using Excel. Social media can now be used as a source of information literacy, especially at the State University level. One form of information literacy media at the Bengkulu university level is the @Unibinfo Instagram media account. One form of implementation is by sharing information content at the university. both from the academic field (student registration, student scholarships, UKT payment procedures, etc.) and general information such as information about lost motorbikes on campus. This information is not only published with video or photo content but also provides a narrative of the event in the caption or information on the announcement letter. text turned into a photo. The results of this research show that the @Unibinfo Social Media Account has proven to be quite good at meeting students' needs in increasing information literacy. Keywords: Instagram, information literacy, digital